If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2 + x) = 96 (2 * 3 + x * 3) = 96 (6 + 3x) = 96 Solving 6 + 3x = 96 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 3x = 96 + -6 Combine like terms: 6 + -6 = 0 0 + 3x = 96 + -6 3x = 96 + -6 Combine like terms: 96 + -6 = 90 3x = 90 Divide each side by '3'. x = 30 Simplifying x = 30
| 3/4x^2+7x+16=0 | | -8x+19=-5 | | 6a=7-4b | | 7=10-3(x-2) | | -27-(-31)=x/4 | | 4/5x=52/3 | | 6x-30-11x=0 | | -27-(-31)= | | 7+14x+60=-13 | | x+18+3x=-19-3x-26 | | 9(x-2)=-18 | | -8y-(2y-3)=9 | | -56/-8= | | (2/5)^4 | | -42/7= | | -8=3x/5+10 | | (-1)(-2)(-3)(-4)= | | 4/3p=5/4p+1/2 | | 9=7y+5 | | 6v-5/8 | | 7n-4=-25 | | 15=16t^2+29t+6 | | 3(-9)= | | 2n+25+5n+29=180 | | 5x(3x+2)=1 | | 3x-9=-2 | | s4+t2+s/2 | | 33-10x=18+5x | | -4w-9=19 | | 4+3w=-2 | | 7+C=9 | | -48/(-6)= |